Effect of innovations in human resource practices, innovation capabilities, and competitive advantage on small and medium enterprises' performance in Thailand - Jedsada Wongsansukcharoen; Jutamard Thaweepaiboonwong (European Research on Management and Business Economics (ERMBE), 2023)
This study examines the performance of wholesale and retail small and medium enterprises in Thailand, which are integrating innovations in human resource practices, innovation capabilities, and competitive advantage. The data sample comprises 260 small and medium enterprises located in the Eastern Economic Corridor, Thailand. The data were analyzed using quantitative and structural equation modeling. The study finds a significant relationship between innovations in human resource practices, innovation capabilities, competitive advantage, and SME performance. The significant success factors of innovations in human resource practices indirectly affect SME performance through the mediation of innovation capabilities and competitive advantage. These outcomes help develop long-term and business performance effectiveness, as the essential human resource factors and innovation capabilities practices of the current extremely competitive industry will intensify with the digital disruption era.
Keywords: M00; M1; M12; M5; O30; 650; Innovations in human resource practices; Innovation capabilities; Competitive advantage; SME performance